Analisis Dampak Lalu Lintas Akibat Perbaikan Jalan Majapahit Semarang: Studi kasus Jalan Majapahit, Kota Semarang - Tarekh Al Aziz; Zuhair Zuhdi; Rachmat Mudiyono; Juny Andry Sulistyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The growth of urban activities in Semarang City has led to an increase in traffic movement, particularly along Jalan Majapahit, which serves as a primary corridor connecting the city center with residential and industrial areas. Road rehabilitation works on this segment caused lane narrowing, resulting in reduced road capacity and affecting overall traffic performance. This study aims to analyze traffic characteristics and road performance on Jalan Majapahit before and during the road rehabilitation period. The evaluated parameters include traffic volume, side friction, road capacity, degree of saturation (DS), and level of service (LOS), based on the Indonesian Road Capacity Guidelines (PKJI 2023). The research method involved field surveys consisting of vehicle volume counts, side friction observations, and geometric road measurements. The collected data were then analyzed to determine road capacity and degree of saturation under both conditions. The results indicate that before rehabilitation, the degree of saturation reached approximately 0.736, representing relatively stable traffic conditions. However, during the rehabilitation period, the DS increased to 1.192, indicating that traffic demand exceeded road capacity, leading to congestion, reduced vehicle speeds, and traffic queues. Consequently, the level of service deteriorated from category C before rehabilitation to category E during rehabilitation